Feasibility and acceptability of Problem Management Plus (PM+) among Syrian refugees and asylum seekers in Switzerland: a mixed-method pilot randomized controlled trial. Issue 1 (31st December 2022) - Spaaij, Julia; Kiselev, Nikolai; Berger, Christine; Bryant, Richard A.; Cuijpers, Pim; de Graaff, Anne M.; Fuhr, Daniela C.; Hemmo, Mahmoud; McDaid, David; Moergeli, Hanspeter; Park, A-La; Pfaltz, Monique C.; et al.
ABSTRACT: Background: Syrian refugees in Switzerland face several barriers in accessing mental health care. Cost-effective psychological interventions are urgently needed to meet the mental health needs of refugees. Problem Management Plus (PM+) is an evidence-based, psychological intervention delivered by trained non-specialist 'helpers'. Objective: To assess the feasibility and acceptability of PM+ among Syrian refugees in Switzerland. Methods: We conducted a single-blind pilot randomized controlled trial (RCT) with Syrian refugees impaired by psychological distress (K10 > 15 and WHODAS 2.0 > 16). Participants were randomized to PM+ or Enhanced Treatment As Usual (ETAU). Participants were assessed at baseline, and 1 week and 3 months after the intervention, and completed measures indexing mental health problems and health care usage. Semi-structured interviews were conducted with different stakeholders. Results: N = 59 individuals were randomized into PM+ ( n = 31) or ETAU ( n = 28). N = 18 stakeholders were interviewed about facilitators and barriers for the implementation of PM+. Retention rates in the trial (67.8%) and mean intervention attendance ( M = 3.94 sessions, SD = 1.97) were high. No severe events related to the study were reported. These findings indicate that the trial procedures and PM+ were feasible, acceptable and safe. Conclusions: The findings support the conduct of a definitive RCT and show that PM+ might have the potential to be scaled-up in Switzerland. The importance, as well as the challenges, of implementing and scaling-up PM+ in high-income countries, such as Switzerland, are discussed. HIGHLIGHTS: The results of this pilot randomized controlled trial suggest that Problem Management Plus (PM+), a low-intensity psychosocial intervention delivered by non-specialized 'helpers' is a feasible, well-accepted and safe treatment option for Syrian refugees in Switzerland.